2020
DOI: 10.1111/1753-0407.13019
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortex brain damage and glycemic control in patients with type 2 diabetes

Abstract: Background: This study examined brain tissue integrity in sites that controls cognition (prefrontal cortices; PFC) and its relationships to glycemic outcomes in adults with type 2 diabetes mellitus (T2DM). Methods: We examined 28 T2DM patients (median age 57.1 years; median body mass index [BMI] 30.6 kg/m 2 ;11 males) and 47 healthy controls (median age 55.0 years; median BMI 25.8 kg/m 2 ; 29 males) for cognition (Montreal Cognitive Assessment [MoCA]), glycemic control (hemoglobin A1c [HbA1c]), and PFC tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…We found significant cognitive impairment in PAH patients, especially in delayed recall, consistent with previous studies 7,32 . Multiple conditions with chronic disorders demonstrated loss of white and GM volume and tissue integrity 12,15,16,19,20,22 . At present, this is the first study that shows significant brain structural (GM volume and brain tissue integrity) changes in PAH patients, which could account for most of the symptomatology presented in the condition.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found significant cognitive impairment in PAH patients, especially in delayed recall, consistent with previous studies 7,32 . Multiple conditions with chronic disorders demonstrated loss of white and GM volume and tissue integrity 12,15,16,19,20,22 . At present, this is the first study that shows significant brain structural (GM volume and brain tissue integrity) changes in PAH patients, which could account for most of the symptomatology presented in the condition.…”
Section: Discussionsupporting
confidence: 89%
“…Among noninvasive brain MRI procedures, high‐resolution T1‐weighted and T2‐relaxometry can be used to examine brain tissue changes. High‐resolution T1‐weighted images are used for voxel‐based morphometry (VBM) analysis, which has been used to assess gray matter (GM) tissue changes in various conditions, including heart failure, obstructive sleep apnea, single ventricle heart disease, Type 2 Diabetes, liver cirrhosis, depression, optic neuritis, panic disorder, obesity, and chronic back pain 12,16–20 . T2 relaxometry measures free water content, and values demonstrate alterations in gray and white matter, with higher T2‐relaxation values indicating chronic tissue changes.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic hyperglycemia and oxidative stress may result in the dysregulation of the internal environment of the cerebral vasculature, resulting in structural changes of the affected areas. The findings of previous studies have demonstrated that patients with early-onset T2DM have lower GMV ( 33 , 34 ), GM density ( 9 , 32 ), and cerebral glucose metabolism ( 9 ). A previous study ( 32 ) on middle-aged to elderly adults also reported the association of reduced prefrontal cortex density with cognitive dysfunction and poor glycemic control, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 95%
“…The findings of previous studies have demonstrated that patients with early-onset T2DM have lower GMV ( 33 , 34 ), GM density ( 9 , 32 ), and cerebral glucose metabolism ( 9 ). A previous study ( 32 ) on middle-aged to elderly adults also reported the association of reduced prefrontal cortex density with cognitive dysfunction and poor glycemic control, which is consistent with our findings. Additionally, the SFG is a region located in the prefrontal cortex that connects other brain regions ( 35 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation